Greater Than Parts : A Metropolitan Opportunity - Mehrotra, Shagun; Lewis, Lincoln; Orloff, Mariana; Olberding, Beth (World Bank, Washington, DC, 2020)
Globally, cities are the source of over 70 percent of the world's greenhouse gas emissions. Cities are also the engines of the global economy, concentrating more than half the world’s population, and they are where the middle class is rapidly expanding. Indeed, by the year 2050, two-thirds of the world will be urban, with cities accommodating an additional 2.5 billion people over today’s total. Nearly all of this urban growth will occur in developing countries. This concentration of people and assets also means that the impacts of natural disasters, exacerbated by the changing climate, may be even more devastating, both in terms of human lives lost and economic livelihoods destroyed. These effects will disproportionately burden the poor. Earth is on a trajectory of warming more than 1.5 degrees Celsius unless important decarbonizing steps are taken.Often urban policymakers prescribe integration as the solution to steering urbanization towards decarbonization to achieve greater global and local environmental benefits. However, little is known about the struggles—and successes—that cities in developing countries have in planning, financing, and implementing integrated urban solutions. The main objective of this report is to understand how a variety of developing and emerging economies are successfully utilizing horizontal integration—across multiple infrastructure sectors and systems—at the metropolitan scale to deliver greater sustainability. This report explores how integrated planning processes extending well beyond city boundaries have been financed and implemented in a diverse group of metropolitan areas. From this analysis, the report derives models, poses guiding questions, and presents three key principles to provoke and inspire action by cities around the world.